A 90-day Sub-chronic Oral Toxicity Assessment of Mulberry Extract in Sprague Dawley Rats. (12th November 2021) - Hong, Min; Lu, Min; Qian, Yimin; Wei, Liping; Zhang, Yaqun; Pan, Xueying; Li, Hua; Chen, Huaying; Tang, Naping
Mulberry extract from Fructus Mori contains an anthocyanin pigment and has been widely used as a food additive in China and other Eastern Asian countries. Only few research has been done on toxicological profiling of mulberry extract for its safety evaluation; however, the data is inconclusive. In the current study, mulberry extract of 4200, 1400, or 466 mg/kg were orally administrated to Sprague Dawley rats for 90 consecutive days followed by a recovery period of 28 days. No abnormalities were detected in body weights, food intake, ophthalmological, hematological, coagulation, clinical chemistry, and organ weights parameters. Discoloration of urine (red, purple, and brown) and feces (black), along with bedding material (purple) were observed in the 4200 mg/kg group. Further, microscopic examination revealed brown granules in the renal tubular cells for rats in 4200 and 1400 mg/kg groups. Since these changes were associated with excretory effect of the extract, the No Observed Adverse Effect Level was determined to be 4200 mg/kg, which was equivalent to the 1058.5 mg/kg of anthocyanin.